Integrated mineralogical and typological study of Axe-God pendants from the Jade and pre-Columbian Culture Museum in Costa Rica - Hernández-Murillo, Camila (2021)
The mineralogical composition and typological classification of a group of 226 Axe-God pendants from the Jade and pre-Columbian Culture Museum (from the Instituto Nacional de Seguros) in San José (Costa Rica) was studied, using a non-invasive characterization technique and a novel stylistic classification scheme. Possible composition-design correlations were examined through descriptive and functional statistical analysis. This study constitutes an initial step towards the comprehensive analysis of this distinctive pendant design.